ICE pocket guide to steels in the built environment - Hall, Stephen J. (ICE Publishing, 2021)
ICE Pocket Guide to Steels in the Built Environment is the quick reference guide to using steels in construction projects and structural design. Over 150 steels and subgrades are listed, with each entry containing its naming convention, steel number and a description of its properties, combined with infographics describing the format in which each steel is available. By neatly and definitively bringing key steel information into the one place, while avoiding manufacturer bias, this guide offers users the opportunity to investigate and specify the right steel for each project, based on the properties required.
Also issued in print: 2021.
Keywords: Building, Iron and steel -- Handbooks, manuals, etc.; elektronické knihy; electronic books